AI in the Era of GPT: Transforming the Future of Work and Discovery - Lavista Ferres, Juan M.; Fishman, Elliot K; Chu, Linda C; Lopez-Ramirez, Felipe; Crawford, Charles K; Rowe, Steven P (Journal of the American College of Radiology, 2025)
In this new era of accelerated discovery and rapid technological advancements, artificial intelligence (AI) stands out as one of the most prominent areas of innovation, transforming how we approach complex problems across different fields. The recognition by the Nobel Prize committee of the recent physics and chemistry laureates, John Hopfield and Geoffrey Hinton, for their role in enabling artificial neural networks is one example that emphasizes the transformative power that AI holds in our time [1]. The capabilities of AI seem to expand as quickly as hardware can provide increased capabilities [2,3]. With such power, AI has inspired a new level of optimism in the scientific community—although many are still skeptical of its potential impact on society [4,5]. That only seems natural, as throughout history, humans have evolved to focus on negative news, adopting a pessimistic outlook as a vital survival mechanism. Indeed, although we are in an era in which the majority of human development metrics—including infant mortality, poverty, and global literacy rates—have been trending in a positive direction for the past several decades, there remains a focus on negative news [6,7].